(Dis)connected by design? Using participatory citizen science to uncover environmental determinants of social connectedness for youth in under-resourced neighbourhoods - Meridith Sones; Meg Holden; Yan Kestens; Abby C. King; Mimi Rennie; Meghan Winters (BMC, 2024)
Abstract Background Social isolation and loneliness are a growing public health concern. Inadequacies in neighbourhood social infrastructure can undermine social connectedness, particularly for youth, who are dependent on their local environments yet often marginalized from public spaces and city planning. Integrating citizen science with participatory action research, the Youth.hood study set out to explore how neighbourhood built environments help or hinder social connectedness from the understudied perspective of youth in under-resourced and racialized communities. Methods Youth (n = 42) from three neighbourhoods in Vancouver, Canada were recruited to: (1) Assess environmental assets and barriers to connectedness in their neighbourhoods using a digital photovoice app; (2) Analyze and prioritize their collective data into themes; and (3) Design and advocate for environmental improvements through a participatory workshop and forum with residents, city planners, and elected officials. Data on participant characteristics and neighbourhood perceptions were collected via an online survey and analyzed descriptively. Participatory analysis was conducted with youth using methods from thematic analysis, photovoice, and design thinking. Results Youth captured 227 environmental features impacting their connectedness. The most frequently reported assets were parks and nature (n = 39, 17%), including formal and informal green spaces, and food outlets (n = 25, 11%). Top barriers included poor neighbourhood aesthetics (n = 14, 6%) and inadequate streets and sidewalks (n = 14, 6%). Thematic analysis with youth underscored four themes: (1) Connecting through mobility: The fun and functionality of getting around without a car; (2) The power of aesthetics: Mediating connections to people and place; (3) Retreating to connect: Seeking out social and restorative spaces for all; and (4) Under-resourced, not under-valued: Uncovering assets for sociocultural connection. Youth described their local environments as affording (or denying) opportunities for physical, emotional, and cultural connection at both an individual and community level. Conclusion Our findings extend evidence on key environmental determinants of social connectedness for youth, while highlighting the potential of community design to support multiple dimensions of healthy social development. Additionally, this work demonstrates the resilience and agency of youth in under-resourced settings, and underscores the importance of honouring assets, co-production, and intergenerational planning when working to advance healthy, connected, and youthful cities.